Hydrogel-Assisted Electrospinning for Fabrication of a 3D Complex Tailored Nanofiber Macrostructure - Eom, Seongsu; Park, Sang Min; Hong, Hyeonjun; Kwon, Jinju; Oh, Sang-Rok; Kim, Junesun; Kim, Dong Sung (American Chemical Society, 2020)
Electrospinning has shown great potential in tissue engineering and regenerative medicine due to a high surface-area-to-volume ratio and an extracellular matrix-mimicking structure of electrospun nanofibers, but the fabrication of a complex three-dimensional (3D) macroscopic configuration with electrospun nanofibers remains challenging. In the present study, we developed a novel hydrogel-assisted electrospinning process (GelES) to fabricate a 3D nanofiber macrostructure with a 3D complex but tailored configuration by utilizing a 3D hydrogel structure as a grounded collector instead of a metal collector in conventional electrospinning. The 3D hydrogel collector was discovered to effectively concentrate the electric field toward itself similar to the metal collector, thereby depositing electrospun nanofibers directly on its exterior surface. Synergistic advantages of the hydrogel (e.g., biocompatibility and thermally reversible sol-gel transition) and the 3D nanofiber macrostructure (e.g., mechanical robustness and high permeability) provided by the GeIES process were demonstrated in a highly permeable tubular tissue graft and a robust drug- or cell-encapsulation construct. GelES is expected to broaden potential applications of electrospinning to not only provide in vivo drug/cell delivery and tissue regeneration but also an in vitro drug testing platform by increasing the degree of freedom in the configuration of the 3D nanofiber macrostructure.